Evaluation of Biomass Production, Nutrient Content and Digestibility of Asystasia gangetica as an Alternative Forage under Palm Plantation - Nur Rochmah Kumalasari; Herilimiansyah Herilimiansyah; Choirul Badriah; Sunardi Sunardi; Lilis Khotijah; Luki Abdullah (Jurnal Ilmu-Ilmu Peternakan, 2023)
Integrated farming systems through inclusion of forage into the plantation area can increase forage supply for ruminants.  The aim of the research was to evaluate biomass production, nutrient, mineral content and digestibility of A. gangetica under different light intensity on palm plantation area. The research was conducted under randomized complete block design based on three different light intensity on each block.  Data were analyzed statistically with R i386 3.6.1 using Analysis of Variance Test (ANOVA), and Duncan Test was applied to determine the level of significant diﬀerence.  The research showed A. gangetica cultivation influenced the soil properties under palm plantation.  A gangetica growth well until light intensity 14.39% that indicated by average biomass production on the first harvest time reached 78.58 g/plant.  The light intensity decreases triggered an increase of A. gangetica dry matter percentage, ash content and crude protein.   The light intensity unaffected the concentration of minerals Ca, P, Mg and forage digestibility, on the other side the dry matter digestibility on the second harvest time decreased due to the soil properties influences. The research concluded that biomass production, nutrient, mineral content and digestibility of A. gangetica under palm plantation area were affected by light intensity, soil properties and harvest time